Malignant lymphoma incidentally diagnosed due to the perforation of the small intestine caused by a fish bone: A case report. (2017) - Hiraki, Masatsugu; Miyoshi, Atsushi; Anegawa, Go; Kubo, Hiroshi; Ikeda, Osamu; Ohira, Keiichi; Azama, Shinya; Kido, Shinichi; Mori, Daisuke; Aibe, Hitoshi; Tanaka, Toshiya; Kitahara, Kenji; et al.
Highlights: Perforation due to an ingested foreign body can occur at some point of physiological narrowing or angulation of the intestinal lumen, such as the ileocecal and rectosigmoid junctions. We experienced an unusual case of malignant lymphoma incidentally diagnosed after perforation of the jejunum by a fish bone. In cases of perforation of the jejunum with an ingested foreign body, careful observation during the surgery may be needed in order to avoid missing the accompanying malignancy. Abstract: Introduction: The ingestion of a foreign body is relatively common. However, it rarely results in the perforation of gastrointestinal tract. We herein report an unusual case of malignant lymphoma incidentally diagnosed after the perforation of the small intestine by a fish bone. Presentation of case: A 90-year-old woman was admitted to our hospital because of abdominal pain and vomiting. Abdominal computed tomography demonstrated free air and ascites in the abdominal cavity. In the pelvic cavity, a radiopaque linear shadow about 35 mm in diameter was shown in the small intestine, and the stricture was exposed to the abdominal cavity. Therefore, a diagnosis of perforation of the small intestine due to ingestion of a foreign body and panperitonitis was made. Emergent laparotomy was performed. The intraoperative findings revealed perforation of the small intestine with a fish bone in the jejunum. Local inflammation at the perforation site was seen, and circulated wall thickness was observed at the distal side of the jejunum. Partial resection of the jejunum and anastomosis of jejuno-jejunostomy was performed. A pathological examination and immunohistochemical study of the resected specimen resulted in a diagnosis of malignant lymphoma of follicular lymphoma Grade 1. Discussion: It is very difficult to identify the existence malignancy accompanied with gastrointestinal perforation with ingestion of a foreign body. Conclusion: In cases suspected of involving malignancy, careful observation during surgery is needed in order to avoid missing the accompanying malignancy.